Clinicopathological Characteristics of Acute Pyelonephritis with or without Renal Failure and Current Status of Antimicrobial Susceptibility (TAJ: Journal of Teachers Association, 2022)
Acute pyelonephritis (APN) is the most common bacterial infection involving the upper urinary tract system, including the renal parenchyma and pelvis. Complications of APN include renal abscess, septic shock, and renal impairment, including AKI. At the same time, antibiotic resistance of uropathogens Resulted in unfavorable clinical responses in APN. The objective of the study was to evaluate the clinical characteristics of patients with APN and antimicrobial susceptibility of causative bacteria. It was a cross-sectional type of observational study which included 100 diagnosed patients of APN admitted into the department of nephrology, Rajshahi Medical College Hospital, Rajshahi, from January 2018 to December 2018. In both males and females, E. coli was the major causative bacteria (51.1% vs. 48.9%). Renal failure was present in 87% of patients, and among them, AKI was present in 81.6% and CKD in 18.4%). Infection with klebsiella was significantly more common among CKD patients as compared to AKI (p